Philo of Alexandria and Greek myth : narratives, allegories, and arguments - Alesse, Francesca (Studies in Philo of Alexandria, 2019)
In Philo of Alexandria and Greek Myth: Narratives, Allegories, and Arguments, a fresh and more complete image of Philo of Alexandria as a careful reader, interpreter, and critic of Greek literature is offered. Greek mythology plays a significant role in Philo of Alexandria's exegetical oeuvre. Philo explicitly adopts or subtly evokes narratives, episodes and figures from Greek mythology as symbols whose didactic function we need to unravel, exactly as the hidden teaching of Moses' narration has to be revealed by interpreters of Bible. By analyzing specific mythologems and narrative cycles, the contributions to this volume pave the way to a better understanding of Philo's different attitudes towards literary and philosophical mythology.